2009
DOI: 10.1194/jlr.m800414-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

PLTP activity is a risk factor for subsequent cardiovascular events in CAD patients under statin therapy: the AtheroGene Study

Abstract: Phospholipid transferprotein (PLTP) mediates both net transfer and exchange of phospholipids between different lipoproteins. Although many studies have investigated the role of PLTP in atherogenesis, the role of PLTP in atherosclerotic diseases is unclear. We investigated the association of serum PLTP activity with the incidence of a combined endpoint (myocardial infarction and cardiovascular death) and its relation to other markers of atherosclerosis in 1,085 patients with angiographically documented coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…This fi nding of poor correlation in male controls not on statin pharmacotherapy is in contrast with prior reports of high concordance ( r = 0.90) between the two methods (36)(37)(38). Similar to the high correlation between HDL-C and HDL-P in MESA ( r = 0.69) but the lack of HDL-C to predict cIMT in a multivariate model including HDL-P ( 7 ), the relative lack of correlation observed between the two PLTPa assays (see Fig.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This fi nding of poor correlation in male controls not on statin pharmacotherapy is in contrast with prior reports of high concordance ( r = 0.90) between the two methods (36)(37)(38). Similar to the high correlation between HDL-C and HDL-P in MESA ( r = 0.69) but the lack of HDL-C to predict cIMT in a multivariate model including HDL-P ( 7 ), the relative lack of correlation observed between the two PLTPa assays (see Fig.…”
Section: Discussioncontrasting
confidence: 55%
“…Additionally, one prospective study of 1,085 participants with angiographically documented CHD at baseline has reported a positive association between PLTPa and the composite outcome of incident MI and death ( 38 ). A separate prospective study of 2,679 participants without known CVD at baseline from the Framingham Heart Study found that PLTP higher than the median was a risk factor for incident CVD in males only ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While studies have associated elevated PLTP with coronary artery disease ( 18 ), left ventricular dysfunction ( 19 ), and coronary artery events in subjects on statins ( 20 ), the opposite result was reported for peripheral artery disease. Peripheral artery vascular disease has been associated with lower PLTP ( 21 ), while carotida intima-media thickness ( 22 ) has been associated with raised PLTP in humans.…”
Section: Pltp Activitymentioning
confidence: 83%